Eine "ecclesiola bohemica" in der sorbischen Lausitz: zu Begegnungen zwischen tschechischsprachigen Exulanten und Lausitzer Sorben im 18. Jahrhundert - Malinkowa, Lubina (Unitas Fratrum, 2018)
Considerable attention has been paid in recent years to the history of Bohemian exiles in Saxony and Lusatia. However, it has remained unnoticed that in Lusatia the Bohemians, most of whom spoke only Czech, in some cases encountered a Sorbian population, the majority of whom spoke only Sorbian. This study therefore investigates the particular relationships and encounters between Lusatian Sorbs and Bohemian exiles. Attention is given to places of encounter such as family, work and church, as well as to the Moravian Church. In the latter attempts were made, especially in view of the lack of suitable leaders who could speak Czech or Sorbian, to make use of synergies between the two nations in congregational work. The idea of founding a Moravian settlement for Sorbs and Bohemians came to nothing, but countless people moved between the Sorbian and Czech congregational work in Kleinwelka, Niesky and Berlin. A further focus of the article is on people who played important intermediary roles, such as the Bohemian-Sorbian-German pastor Georg Petermann, who generated relationships between Bohemians and Sorbs. For example, while working in Upper Lusatia Petermann developed a seminary in Klix for future Sorbian ministers in about 1740, gathered a Bohemian congregation and attracted other Bohemian pastors to come to Sorbian Lusatia.